(r-2)/(r+2)-2r/(r+9)=6?

(r-2)/(r+2)-2r/(r+9)=6

Simplify that to a rational fraction. Please explain the steps. ^_^

1 Answer

Relevance
  • Anonymous
    10 years ago
    Favorite Answer

    [(r-2)(r+9) -2r(r+2)] / [(r+2)(r+9)] = 6

    (r^2 + 7r -18 -2r^2 - 4r) / [(r+2)(r+9)] = 6

    (-r^2 + 3r - 18) / (r^2 + 11r + 18) = 6

    -r^2 + 3r - 18 = 6(r^2 + 11r + 18) = 6r^2 + 66r + 108

    7r^2 + 63r + 126 = 0

    (7r + 42)(r+3) = 0

    r = -6; r = -3

    Using r = -6:

    (-8/-4) - (-12/3) = 6 ==> 2/1 + 4/1 = 6

    Using r = -3

    (-5/-1) - (-6/6) = 6 ==> 5/1 + 1/1 = 6

    • Login to reply the answers
Still have questions? Get your answers by asking now.